What is the central bank effectively targeting in practice? Svensson's concept of inflation forecast targeting and measures of inflation projections - The experiences of selected European countries - Karolina Tura-Gawron (Gdańsk University of Technology, Faculty of Management and Economics, 2016)
This article presents a comparative study of central paths' projections of Consumer Price Index (CPI index), core inflation and monetary policy-relevant inflation measure (MPRI) in the central banks of Sweden, Norway and Czech Republic. The analysis refers to the possibility of using core and MPRI inflation projections as a tool (intermediate goal) for the implementation of Svensson's concept of optimal inflation forecast targeting strategy (IFT) and determines what the chosen central banks are effectively targeting in practice. The study includes a reference of the central paths of the CPI, core inflation and MPRI inflation projections, based on the endogenous rate, to the inflation target. The analysis has allowed us to determine that the central paths of core inflation projections have converged with the inflation target as the time horizon became longer, but still remained medium-term. Such a result is not given for all of the CPI projections. The implications for the implementation of the Svensson's concept of optimal IFT strategy are that a projection of core inflation may be a typical, operational tool which anchors inflation expectations; as such (as CPI projection), it should be published, treated and used as an intermediate goal of monetary policy.
Keywords: E58; E52; E59; 330; core inflation; inflation projection; inflation targeting regime; inflation forecast